2006
DOI: 10.2135/cropsci2005.09-0331
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Evolution of Cultivated Peanut through Crossability Studies among Arachis ipaënsis, A. duranensis, and A. hypogaea

Abstract: Genus Arachis L. includes 80 described species, of which 31 belong to section Arachis, including the two diploid species A. ipaënsis Krapov. and W.C. Gregory and A. duranensis Krapov. and W.C. Gregory, considered the putative B and A genome parents of the cultivated peanut. This work contributes to the study of evolution of the peanut (Arachis hypogaea L.), based on the successful hybridization between A. ipaënsis and A. duranensis, chromosome doubling of the hybrid, and crosses between the synthetic amphidipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
1
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 31 publications
2
135
1
7
Order By: Relevance
“…Arachis monticola, an allotetraploid wild species, considered by some authors to be the ancestor or, alternatively, a derivative of A. hypogaea, also showed susceptibility to P. arachidis. Arachis ipaënsis, one of the original diploid ancestors of A. hypogaea (Fávero et al, 2006), also showed susceptibility to P. arachidis. The variation coefficient was 71.43%.…”
Section: Puccinia Arachidismentioning
confidence: 99%
See 2 more Smart Citations
“…Arachis monticola, an allotetraploid wild species, considered by some authors to be the ancestor or, alternatively, a derivative of A. hypogaea, also showed susceptibility to P. arachidis. Arachis ipaënsis, one of the original diploid ancestors of A. hypogaea (Fávero et al, 2006), also showed susceptibility to P. arachidis. The variation coefficient was 71.43%.…”
Section: Puccinia Arachidismentioning
confidence: 99%
“…It is used mainly for oil and candy production, or for consumption in natura. World production is thought to be more than 30 million tons per year (CONAB, 2003). Brazil has about 90,000 ha planted with peanut, with a production of about 220,000 tons in 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivated peanut (A. hypogaea) is an allotetraploid (2n = 4x = 40) with 2 genome types (A-and B-genome), and thus can be considered to have originated from 2 distinct wild diploid species of Arachis (Kochert et al, 1996). To date, most researchers support the hypothesis that the cultivated peanut originated via hybridization of A. duranensis (A-genome) and A. ipaënsis (B-genome), followed by a rare spontaneous duplication of chromosomes (Halward et al, 1991;Kochert et al, 1996;Fávero et al, 2006;Seijo et al, 2004Seijo et al, , 2007. According to its characteristics, the cultivated peanut is divided into the subspecies A. hypogaea ssp fastigiata and A. hypogaea ssp hypogaea.…”
Section: Studies On Vte3 Of Peanutmentioning
confidence: 99%
“…Finally, the breadth of the peanut genome project to encompass wild diploid as well as cultivated tetraploid species, paralleled by renewed interest in utilizing diploid genetic resources to mine for allelic diversity (Bertioli et al, 2011;Stalker et al 2012Stalker et al , 2013, will promote the use of wild genetic resources in breeding through introgression pathways (Favero et al, 2006;Simpson, 2001). Tom Stalker, North Carolina State University, reviewed the status of wild-species germplasm collections, resistance attributes, taxonomic relationships, crossability, and molecular variation (Stalker et al 2012(Stalker et al , 2013.…”
mentioning
confidence: 99%